Attitude Towards Economic Subjects Among Form Six Students in Segamat District Secondary Schools - Hassan, Muhammad Najmi; Hassan, Haslina (Journal of Social Transformation and Regional Development, 2021)
This study aims to see the extent of the attitude of Form 6 students towards the subject of Economics in three secondary schools in the district of Segamat, Johor. The study was conducted using a questionnaire of 50 items with six-dimensional aspects, namely perceptions of economics teachers, concerns about economics, the importance of economics in society, self-concept in economics, fun in economics, and motivation in economics. Questionnaire data were analyzed using Statistical Package for the Social Science (SPSS) version 25.0. The findings of the study showed that the respondents have a positive attitude towards the perception of Economics teachers with a mean score of 3.93 with a standard deviation of 0.59. Similarly, the positive attitude of the respondents towards the importance of Economics in society with the highest mean score of 3.94 with a standard deviation of 0.56. Other aspects of the respondents’ attitude showed a moderate attitude, namely students’ anxiety towards the subject of Economics with a mean of 2.37, self-concept with the subject of Economics with a mean of 3.42, students’ enjoyment with the subject of Economics with a mean of 3.15 and student motivation towards the subject of Economics with a mean of 3.14. The overall findings of the study showed that the respondents showed a moderate attitude towards the subject of Economics, that is, the average overall mean score was 3.32 with a standard deviation of 0.73. Although not showing a negative attitude, but most of the respondents did not show a positive attitude towards the subject of Economics. The lowest aspect of moderation is students’ anxiety about the subject of Economics.